2016
DOI: 10.1371/journal.pone.0155095
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of DNA Hypermethylation Markers in Peripheral Blood for the Detection of Colorectal Cancer: A Meta-Analysis and Systematic Review

Abstract: DNA hypermethylation in blood is becoming an attractive candidate marker for colorectal cancer (CRC) detection. To assess the diagnostic accuracy of blood hypermethylation markers for CRC in different clinical settings, we conducted a meta-analysis of published reports. Of 485 publications obtained in the initial literature search, 39 studies were included in the meta-analysis. Hypermethylation markers in peripheral blood showed a high degree of accuracy for the detection of CRC. The summary sensitivity was 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…Currently, CRC screening approaches are divided into two categories: Invasive and noninvasive methods. The invasive methods, such as colonoscopy, remain the main screening tools due to their very good diagnostic performance, enabling the detection and removal of precancerous lesions[ 5 ]. However, it requires thorough bowel preparations.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, CRC screening approaches are divided into two categories: Invasive and noninvasive methods. The invasive methods, such as colonoscopy, remain the main screening tools due to their very good diagnostic performance, enabling the detection and removal of precancerous lesions[ 5 ]. However, it requires thorough bowel preparations.…”
Section: Introductionmentioning
confidence: 99%
“…Data from subgroup analysis showed that the pooled sensitivity was higher for studies evaluating SEPT9 methylation than for studies evaluating genes different from SEPT9 (75% vs. 58%) while the pooled specificity was almost comparable (0.89 vs. 0.91). No significant difference among other subgroups including multiple target genes vs. single target gene and qPCR based methods vs. other methods were observed (28).…”
Section: Diagnostic Role Of Circulating Biomarkersmentioning
confidence: 80%
“…Studies examining diagnostic performance of blood markers for CRC detection were systematically reviewed already. 9,25,26 However, these studies did not examine their test performance when combined with FIT. Liu et al 9 waived a conclusion on which biomarker to recommend, whereas Shah et al 25 highlighted the promising results of DNA hypermethylation markers, specifically Septin9 expression and other DNA and microRNA (miRNA) panels.…”
Section: Discussionmentioning
confidence: 99%